Efficacy of Danzhixiaoyao tablets combined with methylcobalamin tablets in the treatment of burning mouth syndrome: an open-label, randomized controlled trial - Ya Gao; Jingwen Yang; Huimin Sun; Haiwen Zhou (BMC, 2024)
Abstract Objectives This randomized controlled trial compared the efficacy and tolerability of danzhixiaoyao pills in the accurate treatment of patients with burning mouth syndrome (BMS). Method Collect a total of 78 patients (75 female patients and 3 male patients) from the oral mucosa department who were considered eligible fromOctober 2020 to October 2022.The patients were randomized and divided into trial group and control group.The trail group received danzhixiaoyao pills and mecobalamine tablets while the control group was given mecobalamine tablets.The Visual Analogue Scale (VAS), Beck Anxiety Inventory(BAI), Beck Depression Inventory (BDI), Oral Health Impact Profile (OHIP-14), Traditional Chinese medicine(TCM) syndrome integral and adverse reactions were performed at baseline and after 2, 4, and 6 weeks of treatment. Descriptive statistics, including the Wilcoxon rank-sum test and the Chi-square test for median comparisons between different times, were used. Result 1.After treatment, the VAS, BDI,OHIP-14, and TCM syndrome integral in the trial group had a significant decrease than the control group(P< 0.05).However, there was no statistical difference in the BAI scores between the two groups (P> 0.05). 2.According to the efficacy determination criteria , the total effective rate of the test group was 73.68% , the control group was 52.94% and the recurrence rate was 0. There was a significant difference between the two groups (Z=-2.688, P < 0.05). The results showed that the curative effect of test group was better than that of control group.3. No adverse effects occurred in patients in either group. Conclusion Danzhixiaoyao pills has demonstrated to have a positive effect in relieving BMS symptoms and in improving a patient's overall quality of life with no AEs compared with the control group. The efficacy evaluation systems that can be verified and complementary in this study provide a perfect, effective and referential evaluation system for the use of Chinese patent medicine in the treatment of oral mucosal diseases. Trial Registration Registry name: Chinese Clinical trail Registry Registration number: ChiCTR2000038189 Date of Registration: 2020-09-13 Please visit ( https://www.chictr.org.cn/showproj.html?proj=61462 ) to the protocol.